Interpretation of scripture: practice : a selection of works of Hugh, Andrew, and Richard of St Victor, Peter Comestor, Robert of Melun, Maurice of Sully, and Leonius of Paris - Hugo, von Sankt Victor (Victorine texts in translation, 2015)
Literal exegesis. Hugh of St Victor, Notes on Genesis / introduction and translation by Jan Van Zwieten -- Introuduction -- Text -- Littera and historia: four texts on the intersection between history and exegesis. Introduction by Frans van Liere and Mark Zier -- Hugh of St Victor: On the three most important circumstances of deeds, that is, persons, places, and times / translation by Grover A. Zinn -- Richard of St Victor: On the concordance of the times of the kings co-ruling over Judah and Israel / translation by Frans van Liere -- Peter Comestor, Historia Scholastica (Chapter 47): the settlement of contrary statements / translation by Frans van Liere -- Andrew of St Victor: Commentary on Daniel, selections / translated by Mark Zier -- The spiritual senses in exegesis and theology: two short theological works of Richard of St Victor. Introduction / by Hugh Feiss, OSB -- Richard of St Victor: On Isaiah: interpreting "He calls to me from Seir" / translation by Hugh Feiss, OSB, and Dale Coulter -- Richard of St Victor: Explanations of several difficulties of Scripture / translation by Hugh Feiss, OSB, and Dale Coulter -- From exegesis to theology. Rober of Melun: Questions on the divine page / introduction and translation by Franklin T. Harkins -- Introduction -- Text -- Hebraica Veritas, Jews and Judaizers. Richard of St Victor: On Emmanuel / introduction and translation by Frans van Liere -- Introduction -- Text -- From texts to sermon: three sermons by Richard of St Victor and Maurice of Sully. Introduction by Hugh Feiss, OSB -- Richard of St Victor: The Book of Notes II.12.5: On the man who went down from Jerusalem to Jericho / translation by Hugh Feiss, OSB -- Richard of St Victor: Sermon 79: On the Day of Pentecost / translation by Hugh Feiss, OSB -- Maurice of Sully: Sermon 35, For the thirteenth Sunday after Pentecost / translation by Hugh Feiss, OSB -- Exegesis and poetry. Leonius of Paris: Histories of the Old Testament: the Book of Ruth / introduction and translation by Greti Dinkova-Bruun -- Introduction -- Text